2009
DOI: 10.1177/0266666909104712
|View full text |Cite
|
Sign up to set email alerts
|

Managing Public Sector Records in Namibia: a proposed model

Abstract: This paper presents an integrated (integrating paper and electronic records) records management programme as a model for managing public service records to support accountability, transparency and good governance in Namibia. Describes the existing records management policies, systems and procedures in the public sector in Namibia and the problems encountered. These problems have been compounded by the increasing reliance on electronic records due to the adoption of the principles and practices of e-government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
3
19
0
Order By: Relevance
“…Retrieving such records when required was reportedly a big challenge. In another study by Nengomasha (2009) on managing public sector records in Namibia, the findings showed that there was lack of storage space for paper records in the selected ministries resulting in congestion and inappropriate storage for semi-current and non-current records consequently affecting service delivery in the ministries. Similarly, Kargo (2009) in a study on the connection between good governance and record keeping in Sierra Leone pointed out that records in all sectors of government were utterly neglected to the extent that it was rumored that in one of the Law Courts, a mermaid was dwelling in the records storage area.…”
Section: Records Storage and Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Retrieving such records when required was reportedly a big challenge. In another study by Nengomasha (2009) on managing public sector records in Namibia, the findings showed that there was lack of storage space for paper records in the selected ministries resulting in congestion and inappropriate storage for semi-current and non-current records consequently affecting service delivery in the ministries. Similarly, Kargo (2009) in a study on the connection between good governance and record keeping in Sierra Leone pointed out that records in all sectors of government were utterly neglected to the extent that it was rumored that in one of the Law Courts, a mermaid was dwelling in the records storage area.…”
Section: Records Storage and Maintenancementioning
confidence: 99%
“…Borrowing from Thurston (2005) computerizationdoes not always provide a panacea for poor records management since it introduces a new range of records management challenges. Furthermore Nengomasha (2009) cautioned that any deficiencies in the management of paper records may be transferred to the management of electronic records if proper planning is not undertaken. The implication for this is that before computerization, the management of paper records should be efficient and effective.…”
Section: Judiciary Strategic Management Planmentioning
confidence: 99%
“…Interviewees are suggesting that effective workforce planning systems be established to determine the immediate staffing needs, and help to ensure that sufficient numbers of RM practitioners are prepared to meet the demands of the RM service. In this study, as with others (Kemoni & Ngulube, 2008;Nengomasha, 2009), the underlying issue in appointing appropriate staffing for RM is connected to the organisational culture and estimated value placed on the function in organisations.…”
Section: Staff Commitment To Public Sector Rm Rolesmentioning
confidence: 75%
“…Since RM is accorded "low" status within entities, and practitioners are often recruited at a "low" level, remuneration is also often "low". This is similar to Nengomasha (2009) MDAs do not appoint staff at the correct level, as the public sector is unable to sustain the ideal number of positions at the Records Manager level. In such cases, administrators will appoint someone as a director of the unit, and then employ Records Officers to support the RM function.…”
Section: Decline Of Staff At the Professional Levelmentioning
confidence: 99%
See 1 more Smart Citation